THE EFFECT OF TEMPERATURE AND STORAGE OF COW'S MILK WATER ON LACTIC ACID LEVELS - Yuyun Nailufar (Universitas Pahlawan Tuanku Tambusai, 2022)
Introduction: Fresh milk is a food that is very high in nutritional value. Cow's milk contains lactose and organic salts secreted by the mammary glands and contains bifidus factor which functions for the growth of Lactobacillus bifidus bacteria which can inhibit pathogenic bacteria. The more lactic acid bacteria in cow's milk, the lower the pH of cow's milk because it produces lactic acid. So that the growth of destructive bacteria and pathogens will be inhibited, so it is possible that an increase in the number of bacteria can provide good durability in cow's milk. Method: This quantitative study aims to determine the effect of temperature and storage time on lactic acid levels in cow's milk. The subject of this research is the milk of dairy cows in the Yogyakarta City farm. The sampling technique that will be used is purposive sampling. The instrument used to measure the levels of lactic acid in cow's milk is a set of titration tools. Analysis of the data used is the calculation of lactic acid levels using the acid-base titration formula. Results: The results of the calculation of the entire sample range from 0.1800 to 0.1890, so that a maximum reference value of 0.2% is obtained. The calculation results for all samples range from 0.1710 to 0.1962, so that a maximum reference value of 0.2% is good. This value can be said that the length of storage of cow's milk for 5 hours at a refrigerator temperature still has a good value for the number of lactic acid bacteria. Conclusion: The effect of temperature before storage on lactic acid levels in cow's milk still has good quantity and quality. The effect of storage time for cow's milk within 5 hours also still has the value and quality of lactic acid levels.